RANCANGAN PEMBELAJARAN BERBASIS KATA SEPAT UNTUK MEMPELAJARI SIFAT-SIFAT SEGI EMPAT - Rini Utami; Nurina Hidayah; Dwi Ario Fajar; Millah Kholishoh (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The aim of this study was to analyze the difficulties of teachers and students in teaching and learning material on the properties of quadrilateral. Based on these difficulties the researcher designed learning activities based on Kata Sepat which would be used to help students understand the material properties of quadrilaterals. The research method used is descriptive qualitative method. The instruments used were interviews and observations. The results of the study showed that teachers and students experienced difficulties in learning and teaching quadrilateral characteristics, so scaffolding was needed in the form of a learning design based on Kata Sepat